2019
DOI: 10.3906/sag-1812-65
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis: epidemiological, clinical and biological profile

Abstract: Background/aim: Hemophagocytic lymphohistiocytosis (HLH) is a clinical, biological, and pathological entity that is rare but has certain morbidity that may be life-threatening. This work aims to establish a focus on the hemophagocytic lymphohistiocytosis and analyze different aspects of diagnosis while emphasizing the biological data. Materials and methods: We report the results of a retrospective study conducted in the hematology department of Avicenna Hospital in Marrakesh. Thirty-one patients with hemophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Notably, children with HLH exhibited significantly higher rates of prolonged fever exceeding 10 days (25% vs. 7.33%, P = 0.0017), hepatomegaly (30.56% vs. 5.08%, P < 0.0001), and splenomegaly (16.67% vs. 1.88%, P = 0.0002) than those without HLH. Past studies by Hanane Zahir and Feig JA reported that approximately 90% of patients with HLH presented with splenomegaly and approximately 61% with hepatomegaly 11 , 12 . This suggests that the presence of hepatosplenomegaly, a common feature in HLH but not sepsis, can aid in distinguishing HLH among patients with sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, children with HLH exhibited significantly higher rates of prolonged fever exceeding 10 days (25% vs. 7.33%, P = 0.0017), hepatomegaly (30.56% vs. 5.08%, P < 0.0001), and splenomegaly (16.67% vs. 1.88%, P = 0.0002) than those without HLH. Past studies by Hanane Zahir and Feig JA reported that approximately 90% of patients with HLH presented with splenomegaly and approximately 61% with hepatomegaly 11 , 12 . This suggests that the presence of hepatosplenomegaly, a common feature in HLH but not sepsis, can aid in distinguishing HLH among patients with sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the revised HLH-2004 diagnostic criteria, to diagnose HLH, a molecular diagnosis consistent with HLH or 5 of the 8 diagnostic criteria for HLH should be fulfilled ( . At the same time, the clinical appearance of these criteria is not always associated with the actual occurrences of HLH, which puts the physician in a difficult situation of making the diagnosis, subsequently leading to unnecessary or incorrect medical procedures and delays in treatment [7,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome characterized by excessive immune activation. Uncontrolled, activated macrophages and T lymphocytes secrete high amounts of cytokines leading to multiorgan failure [ 1 ]. Though usually a disease diagnosed in children, adult cases of HLH are under-recognized and, therefore, undertreated [ 2 ].…”
Section: Introductionmentioning
confidence: 99%